EFFICACY OF PATIENT-ORIENTED CHEMOTHERAPY OF LOCAL TUBERCULOUS LESIONS IN THE CHILDREN EXPOSED TO MULTIPLE/EXTENSIVE DRUG RESISTANT TUBERCULOSIS - M. F. Gubkina; Yu. Yu. Khokhlova; I. Yu. Petrakova; N. V. Yukhimenko (Туберкулез и болезни лёгких)
The objective of the study: to assess the efficacy of patient-oriented chemotherapy of local tuberculous lesions in children exposed to multiple/extensive drug resistant tuberculosis (MDR/XDR TB) based on the results of the immediate and postponed follow-up, and to define the criteria of chemotherapy efficacy in such cases.Subjects and methods: 39 children (3-12 years old) with tuberculosis of chest lymph nodes or focal pulmonary tuberculosis. Patients were randomly divided into two groups treated with different chemotherapy regimens: Group 1 (20 persons) – 5 drugs for the intensive phase / 4 drugs for the continuation phase; Group 2 (19 patients) – 4 drugs for the intensive phase / 3 drugs for the continuation phase. The regimen consisted of the drugs, to which the index case was susceptible. Chemotherapy efficacy was assessed based on the immediate (the ones observed during chemotherapy) and postponed follow-up results (in 1 and 2 years upon treatment completion). The duration of the intensive phase and total duration of treatment were the same in both groups: Group 1 – 3.5 ± 0.5 and 10.5 ± 0.5 months respectively; Group 2 – 3.1 ± 0.6 and 10.0 ± 0.6 months respectively.Results. The efficacy of patient-oriented chemotherapy was confirmed in both groups by results of immediate follow-up and absence of relapses in 1 and 2 years upon chemotherapy completion.Conclusions. The supposed chemotherapy regimens can be used in children with local tuberculous lesions exposed to MDR/XDR tuberculosis as an alternative to standard regimens.